Comparing the efficacy of 2% topical rebamipide and 0.1% topical sodium hyaluronate with or without 0.05% topical cyclosporine in patients with dry eye disease - Priyanka V Gandhi; Omkar Telang; Vrunda Morepatil (Journal of Clinical Ophthalmology and Research, 2021)
Background: Dry Eye Disease (DED) is a multifactorial and complex disease of the ocular surface, with a high prevalence in adults. Aims and Objectives: To compare the efficacy of 2% topical Rebamipide and 0.1% topical Sodium hyaluronate with or without 0.05% topical cyclosporine in patients with dry eye disease (DED). Materials and Methods: This prospective, randomised, comparative, interventional study was conducted at a tertiary level academic centre on 240 eyes of 120 patients having DED, with Schirmer's test (without anesthesia) value less than or equal to 10mm and tear film breakup time (TBUT) less than or equal to 10 secs. After detailed ophthalmic examination, patients were randomly allocated in 4 different groups (A B C D). Group A were given 2% topical Rebamipide, group B received 2% topical Rebamipide with 0.05% topical Cyclosporine, group C were started on 0.1% topical Sodium Hyaluronate and group D were given 0.1% topical Sodium Hyaluronate with 0.05% cyclosporine. Each of these drops was given for 4 times a day for a period of 12 weeks. All patients were followed up after 2 weeks, 4 weeks and 12 weeks. Results: Out of 120 patients, 79 (65.83%) were female and 41 (34.16%) were male. The change in the mean schirmer's score and mean TBUT score was statistically significant in all four groups from baseline to 12 weeks (p<0.05). On comparing with each other, no significance difference was noted in any group. Conclusion: According to our study, 3 months of treatment with either 2% topical Rebamipide or 0.1% sodium hyaluronate is equally effective for DED and addition of 0.05% cyclosporine have no adjunctive role.